2018
DOI: 10.1021/acschemneuro.8b00437
|View full text |Cite
|
Sign up to set email alerts
|

Local μ-Opioid Receptor Antagonism Blunts Evoked Phasic Dopamine Release in the Nucleus Accumbens of Rats

Abstract: Mu-opioid receptors (MORs) in the nucleus accumbens (NAc) can regulate reward-related behaviors that are dependent on mesolimbic dopamine, but the precise mechanism of this MOR regulation is unknown. We hypothesized that MORs within the NAc core regulate dopamine release. Specifically, we infused the MOR antagonist CTAP (D-Phe-Cys-Tyr-D-Trp-Arg-Thr-Pen-Thr-NH2) into the NAc core while dopamine release was evoked by electrical stimulation of the ventral tegmental area and measured by fast-scan cyclic voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In contrast, DOR activation generally increases DA release in the NAc through circuit interactions potentially involving inhibition of KOR signaling ( Svingos et al, 1999 ). MORs are the majority of cell types in the NAc and their activation can increase or decrease NAc DA release through a variety of direct and indirect actions ( Britt and McGehee, 2008 ; Gomez et al, 2019 ).…”
Section: Da Signaling In the Nacmentioning
confidence: 99%
“…In contrast, DOR activation generally increases DA release in the NAc through circuit interactions potentially involving inhibition of KOR signaling ( Svingos et al, 1999 ). MORs are the majority of cell types in the NAc and their activation can increase or decrease NAc DA release through a variety of direct and indirect actions ( Britt and McGehee, 2008 ; Gomez et al, 2019 ).…”
Section: Da Signaling In the Nacmentioning
confidence: 99%
“…The widely supported mechanism through which opioids increase striatal dopamine is via disinhibition of VTA dopamine neurons through MOR‐mediated inhibition of GABA neurons in the rostromedial tegmental nucleus 18,20,21,81,82 . However, there is also evidence that opioids can act locally in the NAc to influence dopamine transmission, with local NAc infusion of fentanyl increasing, and MOR antagonist decreasing, dopamine levels 22,83 . To initially investigate the effects of oxycodone on dopamine transmission in the NAc, we applied oxycodone directly to NAc slices.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,21,81,82 However, there is also evidence that opioids can act locally in the NAc to influence dopamine transmission, with local NAc infusion of fentanyl increasing, and MOR antagonist decreasing, dopamine levels. 22,83 To initially investigate the effects of oxycodone on dopamine transmission in the NAc, we applied oxycodone directly to NAc slices. We found that oxycodone induced a robust MOR-dependent reduction in dopamine uptake, which to our knowledge has not been reported previously.…”
Section: Local Actions Of Oxycodone Reduce Dopamine Uptake In the Nac...mentioning
confidence: 99%
“…Electron microscopy in rodents have suggested that striatal KOR expression is predominantly presynaptic (Meshul & McGinty, 2000), where KOR directly affect DA release (Britt & McGehee, 2008; Clark & Abi‐Dargham, 2019; Werling et al, 1988; Yamada et al, 2006). In contrast, striatal MOR (a main contributor to opioid reward and locomotor effects) is predominantly expressed on GABAergic neurons and interneurons which, among other functions, may indirectly affect DA release (Charbogne et al, 2017; Cui et al, 2014; Gómez‐A et al, 2019). KOR availability accounted for a unique part of variance in striatal patterns of NAL‐ and MRP‐DA release (Figure 4b) which could be consistent with its direct effect on DA terminals whereas striatal MOR availability (measured with PET) may reflect contributions from multiple MOR functions.…”
Section: Discussionmentioning
confidence: 99%